Health mediator model as a way to access to care and health information for Syrian refugees in Turkey. (13th November 2019) - Kayi, I; Şimşek2, Z; Yıldırımkaya, G
Abstract: The number of Syrian refugees residing in Turkey has increased over 200 times since 2012 reaching to 3, 621, 330 (April 2019). Turkey has granted temporary protection status, including access healthcare in the city of registration. Ministry of Health provides on-site health service in temporary shelters, however more than 90% of the Syrian refugees choose to stay in community settings, which along with language barriers limits their ability to access health care and information. With UNFPA we have designed a health mediator model to improve access to health care and awareness on priority concerns such as mental health, reproductive health, child health, health system in Turkey and legal status provided to Syrian refugees. This study is a participatory operational research to test the health mediator model. Operationalization took place in 3 phases: (1) selection and training of Syrian health mediators and provincial coordinators; (2) household visits and data collection; (3) evaluation and supervision. So far, we have trained 174 health mediators from 24 different Turkish cities. Training took 5 days with up to 30 participants each. UNFPA collaborated with NGOs that work with Syrian refugees for coordination purposes. Health mediators made household visits to reach out to Syrian families, gave health education and where necessary support for access to health care services, and conducted a needs assessment. Data collected has been the subject to weekly supervision meetings by local NGOs, health mediators and coordinators to set priorities for the upcoming week. Health mediator model was effective in reaching out to hard-to-reach groups among Syrian refugees, increased health system and legal awareness, contribute to improved healthcare access and prevention of negative health outcomes such as teenage marriages and pregnancies. Inclusion of refugees in decision-making and guidance during the implementation of the project was key for project success.